Korporativno upravljanje in (finančno) računovodstvo - Korošec, Bojana (Organizacija (Kranj), 2011)
In this article, we highlight the relations between accounting or financial reporting respectively and corporate governance based on the role of accounting information as well as the role of the input in several corporate governance mechanisms, and the possible influences of corporate governance on the quality of accounting information. In the light of corporate governance, we also analyse the external financial reporting regulation and underline certain socio-economic implications of the relationship between accounting and corporate governance.
Keywords: podjetja; vodenje; upravljanje; management; računovodstvo; finančno računovodstvo; računovodske informacije